2015
DOI: 10.1590/0103-8478cr20150392
|View full text |Cite
|
Sign up to set email alerts
|

Potencial ornamental de Baccharis milleflora e Baccharis tridentatacomo folhagem de corte

Abstract: RESUMO: A prospecção de novas plantas ornamentais a partir de espécies nativas amplia a oferta de produtos para o mercado da floricultura. Entretanto, antes de uma espécie ser indicada como ornamental, suas características estéticas devem ser avaliadas pelo público consumidor. Com isso, o objetivo deste estudo foi prospectar novas plantas para uso como folhagem de corte e avaliar o seu potencial ornamental. O potencial ornamental das espécies prospectadas foi avaliado por 10 profissionais especialistas em arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Villagra et al (2011), who stated that leaf shape is one of the most important traits for genotypic distinction. Based on Tognon et al (2015), the leaf shape is one of the most relevant elements in arrangements composition since it gives the idea of movement, transmits smoothness (rounded leaves), or even demonstrates aggressiveness (pointy leaves). Leaf size is equally significant in floral arrangements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Villagra et al (2011), who stated that leaf shape is one of the most important traits for genotypic distinction. Based on Tognon et al (2015), the leaf shape is one of the most relevant elements in arrangements composition since it gives the idea of movement, transmits smoothness (rounded leaves), or even demonstrates aggressiveness (pointy leaves). Leaf size is equally significant in floral arrangements.…”
Section: Resultsmentioning
confidence: 99%
“…1). The presence of genetic variability is of great interest since it increases ornamentation usage options (TOGNON, 2015). Additionally, Pietro et al (2012) reported that the green coloration of the species promotes certain lightness to the arrangement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hundreds of species of many botanical families used intensively in commercial floriculture and garden plants and traded commercially as ornamentals (Heywood, 2001). The success of the new floricultural products in the market can be increased if the ornamental desirable traits were determined by specific criteria (Stumpf et al, 2007), such as the morphological characteristics of the plant, as regard to its novelty or aesthetic value (Tognon and Cuquel, 2016). A better understanding of consumers' preferences for native plants, their attitudes toward bringing a more naturalistic landscape design and the assessment of their purchase behaviour may allow a better characterization of the market for producers of native plants (Nils Peterson et al, 2012;Alam et al, 2017).…”
Section: Introductionmentioning
confidence: 99%